ANCIENT MASTERIES AND ANALYTICAL POSITIONS: PSYCHOANALYSIS IN THE LIGHT OF MICHEL FOUCAULT - Iauany, Samuel [UNESP] (My University, 2022)
In order to correlate Foucault and Lacanian psychoanalysis, we analyze part of his final thought, focused on ancient mastery, and shed light on the current question of the psychoanalyst’s position. Our basis consists mainly of the course taught in 1982, published as L’Hermèneutique du Sujet, which significantly addresses the discussion of the therapeutic function of philosophy-a historical-methodological approach that launches Foucault to some analyzes of the present time, among which we find brief references to psychoanalysis. Despite being small, we think that such mentions provide important openings for the dialogue between philosophy and the psychoanalytic field. In addition, we secondarily comment on passages from other courses and conferences from the 1980s, in which the philosopher offers us important tools to think about the role and historical modalities of the dialogical relationship focused on healing, or, in other words, on the relationship between the subject and the truth.
MAITRISES ANCIENNES ET POSITIONS ANALYTIQUES: LA PSYCHANALYSE A LA LUMIERE DE MICHEL FOUCAULT
MESTRIAS ANTIGAS E POSIÇÕES ANALÍTICAS: A PSICANÁLISE À LUZ DE MICHEL FOUCAULT
Keywords: Foucault; Lacan; master; psychoanalyst; the care of the self